2021
DOI: 10.1177/10778012211025993
|View full text |Cite
|
Sign up to set email alerts
|

Nonfatal Strangulation During Domestic Violence Events in New South Wales: Prevalence and Characteristics Using Text Mining Study of Police Narratives

Abstract: Nonfatal strangulation (NFS) is a common form of domestic violence (DV) that frequently leaves no visible signs of injury and can be a portent for future fatality. A validated text mining approach was used to analyze a police dataset of 182,949 DV events for the presence of NFS. Results confirmed NFS within intimate partner relationships is a gendered form of violence. The presence of injury and/or other (non-NFS) forms of physical abuse, emotional/verbal/social abuse, and the perpetrator threatening to kill t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Improved training and awareness from attending police officers can assist in the recording of key details of those involved in a domestic violence event beyond routine demographic and spatio-temporal characteristics and potentially capture information for at-risk sub-populations. Examples of this include reports of mental illness in perpetrators and victims, observed injuries not requiring hospitalization, threats, trends in specific abuse types such as non-fatal strangulation and frequency of abuse within a particular setting such as nursing homes (16)(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved training and awareness from attending police officers can assist in the recording of key details of those involved in a domestic violence event beyond routine demographic and spatio-temporal characteristics and potentially capture information for at-risk sub-populations. Examples of this include reports of mental illness in perpetrators and victims, observed injuries not requiring hospitalization, threats, trends in specific abuse types such as non-fatal strangulation and frequency of abuse within a particular setting such as nursing homes (16)(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated the successful application of text mining to a large corpus of police domestic violence event narratives to identify mentions of mental illness, abuse type(s), and victim injuries ( 16 , 17 ). We also demonstrated that the extracted information can be used to provide insights into domestic violence and mental illness ( 18 ) and in the context specific diagnoses (i.e., autism) ( 19 ), the setting (i.e., nursing homes) ( 20 ), and abuse type (i.e., non-fatal strangulation) ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…These text records enable identification of the characteristics of domestic violence perpetrators (hereafter referred to as Persons of Interest (POIs) i.e., individuals involved in an event that have been accused or charged for perpetrating DV related crimes) that can inform further research, clinical screening, and interventions. Police records enable characteristics of DV events to be described ( 19 ) based on the setting (e.g., nursing homes) ( 21 ), specific mental health conditions (e.g., autism) ( 22 ) and abuse types (e.g., non-fatal strangulation, coercive control) ( 23 , 24 ), and population sub-groups ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies using police data provide demographic information on strangulation within IPV. Wilson, Spike, Karystianis, and Butler (2021) analysed 6,955 Australian-based police records of IPV-related strangulation finding 91.7% of reports noting the perpetrator as male and the victim-survivor as the female, female perpetrator and male victim-survivor in 4.7% of reports, male same-sex couples in 2.5% and female same-sex in 1.1% of cases. Analysing American-based police reports of IPV-related strangulation Messing, Thomas, Ward-Lasher, and Brewer (2021) report similar demographic distribution across different-sex couples, female same-sex and male same-sex couples.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have reported on the diverse range of precipitating events to strangulation, including; emotionally charged arguments, underlying relationship stressors, jealousy, accusations of infidelity, the victim-survivor attempting to end the relationship, substance and alcohol misuse, and the victim-survivor's perceived non-compliance (Bendlin & Sheridan, 2019;Brady et al, 2022;Nemeth, Bonomi, Lee, & Ludwin, 2012;Reckdenwald, Fernandez & Mandes, 2019;Thomas, Joshi, & Sorenson, 2014;Wilbur et al, 2001;Wilson et al, 2021). Notably, as described by Thomas et al (2014), 'mundane demands', such as dinner not being ready or buying the wrong brand of cigarettes, were also described as catalysts for the perpetrator to strangle the research participants.…”
Section: Introductionmentioning
confidence: 99%